Mueller Matrix Ellipsometric Characterization of Nanoscale Subsurface Damage of 4H-SiC Wafers: From Grinding to CMP - Li, Huihui; Cui, Changcai; Lu, Jing; Hu, Zhongwei; Lin, Wuqing; Bian, Subiao; Xu, Xipeng (Frontiers in Physics, 2022)
Subsurface damage of 4H-Silicon Carbide (SiC) wafers, which is detrimental to the performance and lifetime of SiC-based photoelectric devices, is easily induced during surface machining process due to their particular mechanical and physical properties. Nondestructive and effective characterization technique is essential for high quality products in the wafer manufacturing process. A method based on the Mueller Matrix Spectroscopic Ellipsometry (MMSE) is proposed to detect the nanoscale subsurface damage of 4H-SiC wafers induced by grinding and polishing. The Mueller matrix elements which are sensitive to the damage information have been identified through both simulation and experiment. The damage layer and its roughness are considered in optical modeling at different processing stages. The results show that both the surface texture and the damage layer contribute to the Mueller matrix values. The fitting thickness of the damage layer is consistent with the value from Transmission Electron Microscope (TEM); the refractive index of the damage layer matches the surface elements analysis result from X-ray photoelectron spectroscopy (XPS). The results suggest that MMSE-based method could offer a promising nondestructive method to detect global wafer subsurface damaging and its evolution during grinding and polishing, which eventually could benefit process optimization in the whole wafer manufacturing process.